Physical Activity and Mood Responses: Sport Sciences Students - Canikli, Abdullah (Progress in Nutrition, 2021)
Study Objectives: The aim of this study is to examine the correlation between physical activity and mood responses of sports sciences students. 371 female students (age: 21.89 ± 4.33) and 277 male students (age: 22.45 ± 5.44) - 648 in total – participated in the study. Methods: The personal information form developed by the researcher, International Physical Activity Scale (IPAQ) short form for activity levels, and the Brunel Mood Scale for mood responses were used in this study. Results: Findings of the study suggest that males are physically more active and feel more vigorous than females whereas females are physically more inactive than males and experience their negative mood responses more profoundly compared to males. When we analyse physical activity levels and mood responses, we figured out a negative correlation between physical activity levels and negative mood responses. We have also found out a positive relationship between vigorous mood and physical activity levels. Conclusion: Physical activity level of females is lower than that of males, which can be attributed to females experience negative feelings more profoundly. We can also state that males participate in highly intensive exercises more frequently than females do while the increase in their positive mood responses is also higher than that in females. We can suggest that students feel better as the physical activity level goes up and the decrease in physical activity levels of female students will have a negative effect on their lives due to its repercussions on their moods.